Inite Element Analysis For Aluminium Alloy 6061-T4 And Ductile Iron - Lew See Ling (2023)
One of the key components intended to protect passengers from side crashes was a car door, a sort of entrance door that was normally fixed on its outer border but occasionally joined by various devices such as tracks. Aluminium and ductile iron are used in testing of mechanical properties of car door. The objective of the project was to increase the mechanical properties using other materials and compare with steel epoxy using SOLIDWORKS simulation software. SOLIDWORKS simulation was used to calculate the mechanical properties of a material and also to understand the element compositions that gives suitable stress values, displacement and strain. SOLIDWORKS Simulation is a simple set of mechanical analysis software that employ Finite Element Analysis (FEA to simulate CAD models and forecast clear physical behaviour. SOLIDWORKS start with sketch drawing and following by part module and assembly module. After the process, the simulation was start to test the mechanical properties such as displacement, stress and strain of the materials used and get the result finally. Create study, apply materials, restraints and loads, mesh assembly, run simulation and visualize the results. Using SOLIDWORKS simulation software, the mechanical characteristics of the Ductile Iron and the Aluminium Alloy 6061-T4 have been examined, including stress, displacement, and strain. A comprehensive standard report contained the results and the in-depth information. The simulation was completed successfully, according to the results. The Aluminium Alloy 6061-T4 and Ductile Iron will be more economical and environmentally beginning in the future. Keywords: Car door, aluminium alloy 6061-T4, ductile iron, SOLIDWORKS, mechanical properties